THE CONCEPT OF IMÂM IN SHIA IMAMIYYAH PERSPECTIVE - Hendri Hermawan Adinugraha; Ahmad Zayadi; Ahmad Hasan Asy’ari Ulama’i (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2021)
Khilâfah and imâmah are two terms which are sometimes interpreted equally, that is referring to the meaning of leadership. The term of khilâfah is more widely known to be used to the leadership’s term in the Sunni, whereas imâmah is more widely used in the Shiites world of Islam. This article was a literature research that discusses the concept of imâmah in the perspective of Shia Imamiyyah. The analysis technique in this study uses content analysis. The purpose of this article is to describe the political developments among the Shiites that culminate in the concept of imâmah as can be witnessed in Iran until now. The results show that wilâyah al-faqîh which was founded by Imam Khomeini after the Islamic Revolution of Iran has been a form of Islamic government led by a fair and capable faqîh in guiding the ummah. The faqîh leadership model still exists in the Islamic Republic of Iran as a form of a mixture of democracy and religious views. So it can be said that wilâyah al-faqîh was a pilot that politics and religion can be unitedin guiding mankind. [Khilâfah dan imâmah adalah dua istilah yang terkadang dimaknai sama, yaitu merujuk pada makna kepemimpinan. Istilah khilâfah lebih dikenal luas digunakan untuk istilah kepemimpinan di Sunni, sedangkan istilah imâmah lebih banyak digunakan di dunia Islam Syiah. Artikel ini merupakan penelitian literatur yang membahas tentang konsep imâmah dalam perspektif Syiah Imamiyah. Teknik analisis dalam penelitian ini menggunakan analisis isi. Artikel ini bertujuan untuk mendeskripsikan perkembangan politik di kalangan Syiah yang berujung pada konsep imâmah seperti yang dapat disaksikan hingga saat ini di Iran. Hasilnya menunjukkan bahwa wilâyah al-faqîh yang didirikan oleh Imam Khomeini pasca Revolusi Islam Iran merupakan bentuk pemerintahan Islam yang dipimpin oleh seorang faqîh yang adil dan cakap dalam membimbing umat. Model kepemimpinan faqîh masih ada di Republik Islam Iran sebagai bentuk campuran antara demokrasi dan pandangan agama, sehingga dapat dikatakan bahwa wilâyah al-faqîh merupakan percontohan bahwa politik dan agama dapat dipersatukan dalam membimbing umat manusia]